2022
DOI: 10.3389/fendo.2022.913631
|View full text |Cite
|
Sign up to set email alerts
|

Negative Correlation Between 18F-RGD Uptake via PET and Tumoral PD-L1 Expression in Non-Small Cell Lung Cancer

Abstract: PurposeWe investigated the correlation of 18F-AlF-NOTAPRGD2 (18F-RGD) uptake during positron emission tomography (PET) with tumoral programmed death-ligand 1 (PD-L1) expression and explored its potential in immune checkpoint inhibitor treatment.MethodsForty-two mice were subcutaneously injected with CMT-167 lung carcinoma cells. A total of 30 mice with good growth tumor and good general condition were selected. 18F-RGD PET scanning was performed on days 0, 2, 4, 6, 9, and 11 with five mice per day. Immunohisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Several studies have explored the possible correlation between [ 18 ]F-FDG-uptake and existing ICIs sensitivity markers, such as PD-L1 and CD8 + TILs in tumor tissues [ 179 , 180 ]. Our previous study also indicated a correlation between [ 18 ]F-RGD uptake and tumor PD-L1 expression [ 181 ]. Notably, benefiting from its non-invasiveness, PET/CT may also reflect dynamic changes in the TME under ICIs.…”
Section: Irt In Unresectable La-nsclcmentioning
confidence: 84%
“…Several studies have explored the possible correlation between [ 18 ]F-FDG-uptake and existing ICIs sensitivity markers, such as PD-L1 and CD8 + TILs in tumor tissues [ 179 , 180 ]. Our previous study also indicated a correlation between [ 18 ]F-RGD uptake and tumor PD-L1 expression [ 181 ]. Notably, benefiting from its non-invasiveness, PET/CT may also reflect dynamic changes in the TME under ICIs.…”
Section: Irt In Unresectable La-nsclcmentioning
confidence: 84%
“…The radiolabeled cyclic arginine-glycine-aspartate (RGD) peptides can bind to integrin αvβ3 and have been regarded as potent molecular agents for imaging angiogenesis and tumors. It has been reported in non-small cell lung cancer (NSCLC) that higher 18 F-RGD uptake is associated with low PD-L1 expression in tumor cells, and SUV max is the best parameter to display tumoral expression of PD-L1, which indicates that 18 F-RGD PET may be useful for reflecting the immune status [ 35 ]. However, the tumor uptake of RGD-based radiotracers was only moderate.…”
Section: Discussionmentioning
confidence: 99%